Road Traffic Flow Speed on Rural Roads in Latvia - Juris Kreicbergs; Katerina Folla; Juris Smirnovs (The Baltic Journal of Road and Bridge Engineering)
The aim of this article is to perform a comprehensive analysis of the data obtained during flow speed measurements on Latvian national roads. An algorithm for data selection was developed and implemented allowing for an analysis of comparable and unbiased traffic flow measurement data. In the course of the work, more than 150 000 000 traffic flow data records were received from the State Limited Liability Company Latvian State Roads for the period from autumn 2011 to the end of 2022. Above 30 000 000 records from 15 road sites were selected and processed. The results obtained during the analysis were visualized by depicting flow characteristics – average daily traffic, car proportion in traffic flow, average speed, speed histograms, speed rates V25, V50, V75, V90, V95, V99 and proportions of vehicles driven below various speed levels and speeding data. The data characterising the situation on Latvian national roads are intended to be used in the future traffic safety research.